Echocardiographic assessment of left ventricular function in mules under general anesthesia induced with a high-dose xylazine-based protocol - Pannawat Puangsubsin; Ashannut Isawirodom; Porrakote Rungsri; Nuttapon Satumay; Aree Laikul; Worakij Cherdchutham (Veterinary World)
Background and Aim: Echocardiographic assessment in equines is typically performed on standing animals; however, no studies have evaluated left ventricular function in anesthetized mules using high-dose xylazine. Given the unique pharmacokinetics in mules and their higher anesthetic requirements, this study aimed to assess the effects of acepromazine-xylazine-diazepam-ketamine anesthesia, using the upper limit xylazine dose (1.6 mg/kg), on the left ventricular size and function in mules.